Hubungan antara Kadar HbA1c dengan Dislipidemia pada Pasien Diabetes Melitus Tipe II di RSUD Sanjiwani Gianyar - Kadek Kelnerin Pretty Sudirga; Anak Agung Gede Budhitresna; Sri Ratna Dewi (Aesculapius Medical Journal, 2024)
Type 2 diabetes mellitus can cause complications including dyslipidemia. This study was conducted to determine the relationship between HbA1c levels and dyslipidemia in Type 2 Diabetes Mellitus Patients at Sanjiwani Gianyar Hospital. Cross sectional analytic research method was used using secondary data. A total of 81 patients who sought treatment at the Internal Medicine Polyclinic of Sanjiwani Hospital for the period 1 January 2021 - 31 December 2023 were sampled. The results of the analysis using the spearman test with a correlation coefficient value of 0.668 with p = 0.000 (p <0.05) have a strong relationship. The correlation coefficient is positive so that the relationship is unidirectional in both variables, so that if people with Type 2 Diabetes Mellitus have high HbA1c levels, the incidence rate of dyslipidaemia will increase. Based on these results, DM patients are advised to check their lipid profile to prevent dyslipidaemia which can increase the risk of cardiovascular complications and worsen overall health conditions.